2013
DOI: 10.1248/bpb.b12-01004
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Potentiates Apoptosis by Inhibiting Nuclear Factor-kappaB Signaling in H460 Lung Cancer Cells

Abstract: The herbal flavonoid quercetin inhibits the growth of various cancer cells, but how it affects human cancer cells, particularly lung cancer cells, is unclear. We investigated the anticancer activity of quercetin and the underlying molecular mechanisms in non-small cell lung cancer (NSCLC) cells. Quercetin strongly inhibited cell proliferation, and increased sub-G1 and apoptotic cell populations regardless of p53 status. Quercetin-induced apoptosis was verified by caspase cleavage, Hoechst staining, trypan blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 30 publications
2
51
0
1
Order By: Relevance
“…Pretreatment with CMN and QR was found to modulate mitochondrial dysfunction in rodents, and its property as an antioxidant is widely held to be responsible for its protective effects in the mitochondria (Carrasco-Pozo et al 2012;Sood et al 2011). The compound has been described to possess a variety of pharmacological and biological activities including anti-inflammatory (Dai et al 2013;Wang et al 2012), antimicrobial (Kallio et al 2012), antioxidant (Waseem and Parvez 2013;Tang et al 2012), and anticancer activities (Youn et al 2013;Sarkar et al 2010). The mitochondria are the main target for many anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with CMN and QR was found to modulate mitochondrial dysfunction in rodents, and its property as an antioxidant is widely held to be responsible for its protective effects in the mitochondria (Carrasco-Pozo et al 2012;Sood et al 2011). The compound has been described to possess a variety of pharmacological and biological activities including anti-inflammatory (Dai et al 2013;Wang et al 2012), antimicrobial (Kallio et al 2012), antioxidant (Waseem and Parvez 2013;Tang et al 2012), and anticancer activities (Youn et al 2013;Sarkar et al 2010). The mitochondria are the main target for many anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that it has vast pharmacological functions and biological activities such as antioxidant properties, ability to scavenge oxygen free radicals, promote anti-platelet aggregation, lower blood pressure, protect the myocardium against ischemia, prevent ischemic reperfusion injury, enhance immune function, anticancer properties, and antibiosis, anti-virus, and analgesic effects (Youn et al, 2013). Therefore, quercetin is widely used in the treatment of ovarian cancer, breast cancer, white blood cell regulation, gastrointestinal tumors, coronary heart disease, hypertension, and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Kuersetin potansiyel bir anti-kanser ajan olarak umut vadetmektedir. Farklı kanser hücre hatlarında apoptozu aktive ettiği, küçük hücreli olmayan akciğer kanserinde hücre proliferasyonunu güçlü bir şekilde inhibe ettiği ve servikal kanserlerde nF-kB ekspresyonunun azaltılmasıyla apoptotik hücre popülasyonunu arttırdığı gösterilmiştir (64,65). Bu hücrelerde pro-apoptotik Bax proteininin ekspresyonu yanında, sitozolik sitokrom c, Apaf-1 (apoptotic peptidase activating factor 1), p53, kaspaz-9 ve kaspaz-3 ile kesilmiş poli (ADP-riboz) polimeraz (PArP) miktarları da artmıştır.…”
Section: şEkil 4 Kuersetinin Yapısıunclassified